PENGARUH PERSEDIAAN TERHADAP PENJUALAN PADA PT BINA TAMA INTI BUSANA (Studi Empiris pada PT Bina Tama Inti Busana tahun 2010-2015) (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2018)
In general, companies in carrying out their business in trade, of course, inventory of merchandise is very prominent in supporting the course of trade. Sales is one of the important activities in a trading company because the results of the sale of a company can be assessed whether or not good in running its business. This research aims to analyze the effect of inventory on sales both simultaneously and partially on BTIB companies in the textile trade in Jakarta. The type of data used in this study is secondary data. The data analysis method used is a simple linear regression analysis (R), the coefficient of determination (R2), the classic assumption test, the regression coefficient test, the hypothesis test, the F statistical test, the statistical test t. The result shows that a significant influence of Inventory (X) on Sales (Y).